Intracardiac electrophysiology to characterize susceptibility to ventricular arrhythmias in murine models - Ferrand, Marine C.; Giordano, Gauthier; Mougenot, Nathalie; Laporte, Pierre-Léo; Vignier, Nicolas; Leclerc, Arnaud; Algalarrondo, Vincent; Extramiana, Fabrice; Charpentier, Flavien; Neyroud, Nathalie (Frontiers in Physiology, 2024)
Sudden cardiac death (SCD) and ventricular fibrillation are rare but severe complications of many cardiovascular diseases and represent a major health issue worldwide. Although the primary causes are often acute or chronic coronary diseases, genetic conditions, such as inherited channelopathies or non-ischemic cardiomyopathies are leading causes of SCD among the young. However, relevant experimental models to study the underlying mechanisms of arrhythmias and develop new therapies are still needed. The number of genetically engineered mouse models with cardiac phenotype is growing, making electrophysiological studies in mice essential tools to study arrhythmogenicity and arrhythmia mechanisms and to test novel treatments. Recently, intracardiac catheterization via the jugular vein was described to induce and record ventricular arrhythmias in living anesthetized mice. Several strategies have been reported, developed in healthy wild-type animals and based on aggressive right ventricular stimulation. Here, we report a protocol based on programmed electrical stimulation (PES) performed in clinical practice in patients with cardiac rhythm disorders, adapted to two transgenic mice models of arrhythmia -Brugada syndrome and cardiolaminopathy. We show that this progressive protocol, based on a limited number of right ventricular extrastimuli, enables to reveal different rhythmic phenotypes between control and diseased mice. In this study, we provide detailed information on PES in mice, including catheter positioning, stimulation protocols, intracardiac and surface ECG interpretation and we reveal a higher susceptibility of two mouse lines to experience triggered ventricular arrhythmias, when compared to control mice. Overall, this technique allows to characterize arrhythmias and provides results in phenotyping 2 arrhythmogenicdisease murine models.